PENYEBAB MASYARAKAT TIDAK MENCATAT PERKAWINAN DI KECAMATAN LUBUK TAROK KABUPATEN SIJUNJUNG - Elfika, Lia; Rianto, Slamet; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
This study aims to determine the cause of the community does not record the marriage in the District of Tarok Lubuk Sijunjung district. This research is descriptive. The population in this study were all people who did not record the marriage in Tarok Lubuk District Sijunjung ie 606. Samples were taken with a proportional random sampling technique by 15%, so that the population of as many as 91 families who do not register the marriages. The research found that: 1) the economic condition of the people who did not record the marriage in the District of Tarok Lubuk seen major job and the majority of farmers do not have a second job, income / month average of Rp 500,000 - Rp 1.000.000, subsistence needs, mediocre, 4 person family size, sources of revenue aided by his wife, family income in 1 month on average Rp 1,000,000 - Rp 2,000,000 to Rp large expenditures including 939 000 - Rp 1,230,000, 2) access public transportation are not recorded marriage in the District Lubuk Tarok, type of gravel roads impassable roads, means of transport used motorcycles, frequency through the house 3-6 times in one month, the distance from the highway> 75 m, the condition of the house is generally in places where the slope and distance from home KUA office more than 1.5 km and 3) Service in the marriage registration can be done at the office of trustee villages, KUA office services given the generally perceived well enough that people are quite satisfied with the service KUA office but most people feel the cost for payment in the office KUA is still quite expensive. It is recommended to the people who do the registration of marriages in the local KUA. For KUA officials provide the best services to the people who take care of their marriage registration